Pelatihan Responsive Web Design Dengan Menggunakan HTML Dan CSS Pada SMK Tritech Informatika Medan - Putri, Dini Ridha Dwiki; Fahlevi, Muhammad Reza (LPPM Universitas Potensi Utama, 2023)
Developments in technology and information in the world of website design require students to be able to master the skills needed, especially in designing website layouts. Responsive Web Design is a technique that can make the web-based application design process more dynamic and easy to use on various types of devices. This is because using Responsive Web Design allows the screen resolution, density, and aspect ratio on the website to follow the screen ratio of the device. To make it easier to make a website more attractive and it doesn't take too long, it is necessary to take advantage of the use of HTML which helps regulate the appearance of a website and CSS which helps improve the content to make it more colorful. This Community Service conducts training on making Responsive Web Design using HTML and CSS for students of Tritech Informatics Vocational School in Medan. The method used is in the form of training accompanied by hands-on practice using HTML and CSS on the website layout used. This activity began by conducting a survey on the needs of the training participants to map the needs and expectations obtained from the training participants. Most of the participants stated that the material presented in the training was in accordance with the needs of the participants and 85% of the participants were able to design Responsive Web Design using HTML and CSS. Therefore, similar training activities must be carried out continuously so that students' understanding and skills become more comprehensive and students' confidence in interacting with computer media becomes higher.